The Mārkaṇḍeya-purāṇam = Mārkāṇḍeyamahāpurāṇam : Sanskrit text, English translation with notes, and index of verses - Pargiter, F. E.; Jośī, Kanhaiyālāla (Parimal Sanskrit series ;)
Hindu mythological text with English translation.